2017
DOI: 10.1272/jnms.84.110
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Active Treatments for Toxic Epidermal Necrolysis

Abstract: Toxic epidermal necrolysis (TEN) is a severe adverse drug reaction associated with the separation of skin and mucous membranes at the dermal-epidermal junction. Although it is rare, many treatments have been trialed because of its high mortality rate. Active interventions performed to date include the use of systemic corticosteroids, intravenous immunoglobulins (IVIg), cyclosporine, plasmapheresis, antitumor necrosis factor drugs and N-acetylcysteine, but none has been established as the most effective therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…In recent times, there have been numerous studies [12][13][14] that have supported the effectiveness and safety of IVIg. IVIg contains anti-Fas antibodies that inhibit the Fas/Fas ligand (FasL) interaction [6]. We used a combination of high dose systemic corticosteroids and IVIg because of higher age of patient and SCORTEN 4 in our case according to the study results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, there have been numerous studies [12][13][14] that have supported the effectiveness and safety of IVIg. IVIg contains anti-Fas antibodies that inhibit the Fas/Fas ligand (FasL) interaction [6]. We used a combination of high dose systemic corticosteroids and IVIg because of higher age of patient and SCORTEN 4 in our case according to the study results.…”
Section: Discussionmentioning
confidence: 99%
“…A score called SCORTEN developed by Bastuji-Garin et al [5] determines the variables as predictors of prognosis and risk of death in patients with TEN. Systemic corticosteroids, intravenous immunoglobulins (IVIg), cyclosporine, plasmapheresis, antitumor necrosis factor drugs are the treatment options [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there is disagreement between the results of patients treated with corticosteroids, these differences may be due to the variation in the dose administered, duration, and time of evolution of the clinical picture in which it was administered. 24 A Third-level pediatric hospital in Thailand reported that despite being corticosteroids the treatment of choice to reduce excessive immune response, their retrospective study at 20 years did not find an increase in the efficacy of use with corticosteroids and symptomatic treatment 25 . Concluding that the administration of corticosteroids is not recommended as a single therapy in cases of SJJ and TEN.…”
Section: Systemic Treatment • Corticosteroidsmentioning
confidence: 99%
“…Recent studies show an increase in predicted mortality, and its use with anti-TNF can, contrary to what was thought, diminish its effect. 24…”
Section: • N-acetylcysteinementioning
confidence: 99%
“…ТЭН -заболевание с тяжелым тотальным эритематозно-буллезным поражением кожи и слизистых оболочек; в большинстве случаев это результат воздействия лекарственных средств или их метаболитов [3]. Есть данные о манифестации ТЭН на фоне эндотоксемии при тяжелых инфекционных осложнениях.…”
Section: обсуждение результатов леченияunclassified